98.7k views
2 votes
If f(x) = (x + 5), find the inverse of f.f -1(x) = x + 5f -1(x) = x - 5f -1(x) = x/5f -1(x) = 5x

If f(x) = (x + 5), find the inverse of f.f -1(x) = x + 5f -1(x) = x - 5f -1(x) = x-example-1
User Lukiller
by
4.8k points

1 Answer

5 votes

f^(-1)(x)=x-5

1) Let's find the inverse function of f(x) through the following steps


\begin{gathered} f(x)=(x+5) \\ \\ y=x+5\:\:\:Swap\:the\:variables \\ \\ x=y+5 \\ \\ -y=-x+5 \\ \\ y=x-5 \\ \\ f^(-1)(x)=x-5 \end{gathered}

So, in short, we swap the variables, solve for y and replace y with the proper notation.

If f(x) = (x + 5), find the inverse of f.f -1(x) = x + 5f -1(x) = x - 5f -1(x) = x-example-1
User Bharat Kul Ratan
by
4.8k points